Maximizing the World Bank Group’s Impact in the Middle East and North Africa - World Bank Group (World Bank, Washington, DC, 2015)
This report provides an overview of the World Bank Group’s engagement in the Middle East and North Africa (MENA) region, highlighting the new operating model of the World Bank Group. In particular, the report provides insight on the key challenges and strategic engagement of each sector (Global Practice) in MENA and details some of the key cross-cutting challenges that countries face. This report serves as a basis to convene international thought leaders, as well as internal and external stakeholders, in the context of developing a new strategy for the Middle East and North Africa region later this year. The region faces three challenges in particular: (a) long-standing distortions that have generated jobless growth and poor service delivery as well as low financial access and inclusion; (b) severe imbalances that threaten macroeconomic stability; and (c) deep political and social tensions, at times escalating into violent conflict. The World Bank Group’s current engagement supports four key pillars: (a) strengthening governance; (b) ensuring economic and social inclusion; (c) creating jobs; and (d) accelerating sustainable growth. Progress on these pillars can be made through a two-pronged approach focused on addressing the immediate needs arising from humanitarian crises throughout the region while also giving sustained attention to the investments and reforms needed for medium- and long-term development. This two-pronged approach is necessary to help governments cope with immediate pressures on already fragile institutions and at the same time develop long-term strategies to address deep-seated issues that have hindered inclusive growth and prosperity for decades. This report details nine specific cross-cutting challenges: climate change; decentralization; disaster risk management; fragility, conflict and violence; fuel subsidies and social safety nets; gender; governance and service delivery in health and education; private sector development and job creation; and public-private partnerships. Looking ahead, responding to the changing realities on the ground, the World Bank Group is rethinking its regional strategy in order to maximize its impact in the Middle East and North Africa. This new strategy, which is currently under preparation, will aim to step up the Bank Group’s engagement in the region in order to achieve shared growth and prosperity, as well as work with partners to convene change in the region.